COMPARATION BETWEEN PREDICTION EQUATIONS OF TOOL DRAUGHT OF CHISEL PLOWS - ALBIERO, Daniel; MACIEL, Antonio J.S. (Revista Brasileira de Engenharia de Biossistemas, 2010)
This work has the objective to compare tools draught equations with experimental data. It had been used data relative the chisel plows, these values it had been compared with values calculated for the equations. The results show which in general these equations super-dimensioning the tool draught offered for the chisels plows.